2014
DOI: 10.1007/s11882-014-0428-6
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Allergens for Diagnosis of Cockroach Allergy

Abstract: Molecular cloning of cockroach allergens and their expression as recombinant proteins have allowed a better understanding of the mechanisms of cockroach allergic disease. Recombinant cockroach allergens have been used for skin testing or in vitro methods to measure IgE antibody levels in serum. Early studies evaluating selected U.S. patients revealed that a cocktail of four cockroach allergens, Bla g 1, Bla g 2, Bla g 4, and Bla g 5, would identify 95 % of cockroach allergic patients. More recent studies point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 99 publications
(101 reference statements)
0
25
0
4
Order By: Relevance
“…However, other allergen sources such as cockroach do not have a dominant allergen. Early studies revealed that Bla g 1, Bla g 2, Bla g 4, and Bla g 5 identify ~95 % of cockroach-allergic patients in the USA [103]. As more allergens have been identified around the world, different patterns of IgE sensitization to cockroach have been found in other populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other allergen sources such as cockroach do not have a dominant allergen. Early studies revealed that Bla g 1, Bla g 2, Bla g 4, and Bla g 5 identify ~95 % of cockroach-allergic patients in the USA [103]. As more allergens have been identified around the world, different patterns of IgE sensitization to cockroach have been found in other populations.…”
Section: Introductionmentioning
confidence: 99%
“…IgE reactivity to cockroach tropomyosin was found to be dominant in Brazil [27]. Overall, a cocktail of five cockroach allergens from groups 1, 2, 4, 5, and 7 would allow to diagnose 50–65 % of patients worldwide [103]. …”
Section: Introductionmentioning
confidence: 99%
“…These recombinant allergens can not only serve as accurate diagnostic agents, 32, 33 but also can facilitate safe and effective immunotherapy. 15, 16 In this study recombinant Aed a 3 was proved to be an excellent candidate for use in in vivo and in vitro tests with 100% specificity in mosquito bite-negative individuals for the diagnosis of mosquito allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Amerikan hamamböceğine yönelik immünoterapi uygulamalarına, major allerjen ve tüm vücut ekstraktını içeren lipozom-adjuvanlı intranazal kullanılan aşılar eklenmiştir (49). Yine tüm bu zorluklardan dolayı, teşhis ve tedavide kullanılacak rekombinan allerjenler geliştirilmeye çalışılmaktadır (50 Hamamböceğine duyarlı ve evlerinde maruz kalmaya (Bla g 1 düzeyi: ≥2 U/g) devam eden bir grup hastanın Omalizumab'tan çok faydalandığı görülmüştür. Omalizumab verilenlerde, alevlenmeler %71.2 oranında azalmış, semptomlarda büyük oranda azalma ve steroid dozunda büyük düşme saptanmıştır.…”
Section: Literatürdeki Yeni Tedavi Yaklaşımlarıunclassified